2018
DOI: 10.1038/s41418-018-0153-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulating BRCA1 protein stability by cathepsin S-mediated ubiquitin degradation

Abstract: Cathepsin S (CTSS) is a cysteine protease that is thought to play a role in many physiological and pathological processes including tumor growth, angiogenesis, and metastasis; it has been identified as a radiation response gene. Here, we examined the role of CTSS in regulating the DNA damage response in breast cancer cells. Activating CTSS (producing the cleavage form of the protein) by radiation induced proteolytic degradation of BRCA1, which ultimately suppressed DNA doublestrand break repair activity. Deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…As discussed above, hyperglycemia-induced cardiomyocyte damage is associated with ER stress and NF-κB signaling pathway activation [23,24]. Accordingly, we observed alterations in ER stress and NF-κB activation in response to Exenatide treatment.…”
Section: Exenatide Inhibits Er Stress and The Nf-κb Signaling Pathwaysupporting
confidence: 64%
“…As discussed above, hyperglycemia-induced cardiomyocyte damage is associated with ER stress and NF-κB signaling pathway activation [23,24]. Accordingly, we observed alterations in ER stress and NF-κB activation in response to Exenatide treatment.…”
Section: Exenatide Inhibits Er Stress and The Nf-κb Signaling Pathwaysupporting
confidence: 64%
“…Meanwhile, Burton et al (2017) linked nuclear Cathepsin L with CUX1 proteolytic processing and thus linked Cathepsin L with EMT (and MET) progression in BC and PC cells [142]. Interestingly, in this study subcellular Cathepsin L was also observed to translocate from the nucleus to the cytoplasm, highlighting a novel protein trafficking-function for Cathepsin L. Kim et al (2018) showed that Cathepsin S could bind BRCA1 and facilitate it's ubiquitination and breakdown, thus suppressing DNA repair in BC development, while knocked-down expression of Cathepsin S stabilized BRCA1 levels, thus collectively linking Cathepsin S to BRCA1 signaling transduction [143]. As a novel substrate, Bian et al (2015) found Cathepsin B to colocalise and target p27 kip for degradation in CRC cells, thus linking it to cell cycle modulation [144].…”
Section: Signal Transduction Intermediates and Cathepsin Regulationmentioning
confidence: 52%
“…In addition, BRCA2 is becoming ubiquitinated and degraded during tumorigenesis which contributes to genomic instability and development of non-familial cancers 13, 139. A number of proteins have been identified as regulators of BRCA1/BRCA2 stability including cysteine protease Cathepsin S (CTSS) which interacts with the BRCT domain of BRCA1 and activates its proteolytic degradation 140, E2 ubiquitin-conjugating enzyme E2T (UBE2T) 139, E3 ubiquitin ligases Herc2 and F-box-protein 44 (FBXO44) which ubiquitinate and downregulate BRCA1 protein 141, 142. Interaction with BARD1 protein results in the reduction of proteasome-sensitive ubiquitination and stabilization of BRCA1 expression 143.…”
Section: Biological Function Of Brca1 and Brca2mentioning
confidence: 99%